Post-menopausal Sertoli-Leydig cell tumour: a report of two cases - Jacob, Ancy T.; K., Jumanath A.; I., Praseeda; Thomas, Merin; Mathew, Tilka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Ovarian Sertoli-Leydig cell tumors (SLCTs) represent less than 0.2 percent of all ovarian cancers and are an uncommon type of sex cord–stromal malignancy. Since these tumors are discovered in young women at an early stage, the management challenge is in striking the correct balance between a treatment that is effective enough to stop recurrences but yet permits fertility preservation. We present 2 case report of patients, one presented with hirsuitism and on evaluation found to have elevated levels of serum total testosterone and suspicion of SLCTs in magnetic resonance imaging (MRI) pelvis. Total laparoscopic hysterectomy (TLH) was done with bilateral salpingo-oophorectomy (BSO) and histopathology report came as ovarian Leydig cell tumour. Second case with postmenopausal bleeding and on evaluation MRI report showed right ovarian solid tumour-fibroma/fibrothecoma. Tumour markers were normal. TLH was done with BSO, histopathology report came as ovarian SLCT.